2022
DOI: 10.1080/21645515.2022.2054260
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of COVID-19 vaccination among college students: A systematic review and meta-analysis of willingness, associated determinants, and reasons for hesitancy

Abstract: The significance of COVID-19 vaccine has been declared and this study synthesizes the attitudes and determinants in vaccination hesitancy of college students. We searched in PubMed, Web of Science, Cochrane Library and CNKI to enroll the related studies. The modified NOS was used for quality evaluation. Proportion and OR with 95% CI were pooled to estimate the acceptance rates and determinants of COVID-19 vaccination. Data of 34 studies involving 42 countries were pooled. The pooled acceptance rate of COVID-19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
65
1
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(84 citation statements)
references
References 86 publications
2
65
1
2
Order By: Relevance
“…To better analyze the underlying preference disparities, we conducted sub-group analysis based on student majors (humanities/social science or non-humanities/social science) and risk tolerance (risk tolerant or risk adverse). Our results support previous online survey studies which reported that there are no statistically significant relationships between student majors and vaccine preferences ( 26 ). Given our academic major data are social science and non-social science, our results do not contribute to the prior findings that medical and nursing students had higher vaccine willingness than other students due to higher knowledge levels and better perception of vaccines ( 28 , 38 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…To better analyze the underlying preference disparities, we conducted sub-group analysis based on student majors (humanities/social science or non-humanities/social science) and risk tolerance (risk tolerant or risk adverse). Our results support previous online survey studies which reported that there are no statistically significant relationships between student majors and vaccine preferences ( 26 ). Given our academic major data are social science and non-social science, our results do not contribute to the prior findings that medical and nursing students had higher vaccine willingness than other students due to higher knowledge levels and better perception of vaccines ( 28 , 38 ).…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, most mainland Chinese students' COVID-19 vaccination studies, encompassing vaccination acceptance, willingness and hesitancy, mainly used non-DCE online surveys ( 21 25 ), reporting similar vaccine hesitancy factors ( 21 25 ). In terms of student vaccine heterogeneity, the existing literature suggests that student majors do not contribute to differing vaccination preferences ( 26 ), except for medical or nursing students who exhibit overall higher vaccination willingness ( 27 , 28 ). Two DCE studies identified efficacy, safety, number of doses, origin of vaccine and costs in student vaccination preferences, but for students in Hong Kong ( 29 , 30 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although the results on unwillingness to get vaccinated show that one in five people in Canada does not plan to get vaccinated, systematic reviews from other countries have shown even more unwillingness. 57 , 58 , 59 , 60 A systematic review including 46 independent samples from studies conducted in the United States found that only 61% of people were willing to be vaccinated. 57 Results from three systematic reviews of students from 42 countries (69%), 58 33 low‐ and middle‐income countries (LMICs) (58.5%), 59 and one from 30 countries (66.01%) also found low rates of willingness to be vaccinated.…”
Section: Discussionmentioning
confidence: 99%
“… 57 , 58 , 59 , 60 A systematic review including 46 independent samples from studies conducted in the United States found that only 61% of people were willing to be vaccinated. 57 Results from three systematic reviews of students from 42 countries (69%), 58 33 low‐ and middle‐income countries (LMICs) (58.5%), 59 and one from 30 countries (66.01%) also found low rates of willingness to be vaccinated. Interestingly, the rate of vaccine hesitancy is higher in Canada (41.8%) compared with the rate observed in LMICs (38.2%).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research suggests that students with higher levels of COVID-19-related knowledge also had a higher vaccination intention. 27 , 29 We conclude that obtaining adequate information regarding COVID-19-related topics is a key component of having a better general understanding of the complexity of the pandemic and of political decisions made during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 94%